Searching for Soul : A Survivor's Guide - Tyler, Bobbe, 1932- (Book collections on Project MUSE., 2009)
To dive deep into your inner life. To navigate its complexity and explore your story in depth. To discover who you are exactly-the courage you have when life breaks apart, how conscious you become in that process, and how rich you feel learning the meaning of your life. On a search for wholeness, Bobbe Tyler delves deep to find and tell her story-the trauma of familial mental illness, marriage and divorce, spiritual despair, accountability, addiction and the joy of recovery, surviving loss, and finally that which matters most: love in all its ways. The rewards of her wisdom belong not to her.